Comparison of hemodynamic effects of intravenous labetalol plus intravenous fentanyl and intravenous fentanyl alone for attenuating reflex responses to laryngoscopy and intubation: A prospective randomized controlled trial - Jain, Isha; Satyendra Singh Yadav; Shakti Singhal; Jaykumar Kolewar; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: Laryngoscopy is an essential part of endotracheal intubation. Direct laryngoscopy and tracheal intubation are a noxious stimulation that causes significant stress response for patient. It is this nociceptive response which leads to the changes in the physiologic parameters of the patient like hemodynamic changes. Therefore, combination of many drugs used with the primary anesthetic drug in an attempt to minimize the hemodynamic pressor response associated with intubation while limiting patient risk. Aims and Objectives: Direct laryngoscopy and tracheal intubation are the nociceptive response which leads to the changes in the hemodynamic parameters. Study aimed to compare the hemodynamic response of labetalol and fentanyl with only fentanyl during laryngoscopy and intubation, untoward adverse effects. Materials and Methods: One hundred and two of either sex, aged between 18 and 65 year of the American Society of Anesthesiology grade I/II under general anesthesia divided into two groups, Group LF and Group F with 51 patients in each. Group LF receives intravenous 0.25 mg/kg labetalol in 10 mL saline 5 min prior and fentanyl 2 μg/kg 3 min before intubation and Group F receives intravenous normal saline 10 mL 5 min before intubation and 2 μg/kg fentanyl 3 min before intubation. Changes in heart rate (HR), blood pressure, and saturation of oxygen in the blood documented in both the groups. Results: In the present study, HR, systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure were noted down as before intubation, after intubation, at intubation, immediately after 1, 3, 5, 10, and 15 min for patients in both the groups. The results obtained from the analysis showed that there was an increase in parameters of Group F compared to Group LF as after intubation to 15 min due to stress response and statistically significant (P<0.05) in both the groups. Conclusion: Both labetalol and fentanyl can be used safely to attenuate the hemodynamic response, but labetalol and fentanyl combination prove to be more effective in attenuating hemodynamic response.